A special plastic composite material for new energy battery shell and preparation method
By using high-performance resins such as polyphenylene ether resin and meta-aramid fibers, combined with magnesium hydroxide/graphene intercalation organically modified montmorillonite as modified fillers, a plastic composite material for new energy battery shells was prepared, which solved the problems of flammability and processing difficulty of traditional battery shell materials, achieved higher flame retardant and thermal conductivity, and improved the safety and production efficiency of battery shells.
Patent Information
- Application Number
- CN202411530102.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Traditional battery shell materials have flammability problems, resulting in a decrease in safety of new energy vehicles, and the processing is difficult or heavy, which increases production costs.
Polyphenylene ether resin, polyketone resin, polyamide resin, high impact polystyrene resin and metaara fiber are used, and organically modified montmorillonite is used as a modified filler to form a plastic composite material with excellent flame retardant and thermal conductivity.
It improves the flame retardant and thermal conductivity of the battery case, enhances the safety and performance stability of the material, and reduces production costs.
Smart Images

Figure BDA0005110270410000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and in particular relates to a special plastic composite material for new energy battery shells and a preparation method thereof. Background Art
[0002] With the booming development of the new energy vehicle market, the advancement of battery technology has become a key factor driving this trend. As an important component to protect battery safety, the selection and design of the battery casing material has a direct impact on the performance of electric vehicles.
[0003] The battery housing is an integral part of electric vehicles. It not only houses high-voltage batteries, electronic components, sensors and connectors, but also protects these key components from external impact, high temperature and water seepage. The design of the battery housing needs to consider waterproof and airtightness, stability, corrosion resistance and good insulation.
[0004] Traditional battery shell materials mainly use high-strength aluminum alloy, titanium alloy, steel, etc. Among them, aluminum alloy and titanium alloy have the advantages of high strength and high corrosion resistance, but they are difficult to process and require precise processing technology, which will increase production costs; steel has the advantages of low cost and easy processing, but it is heavy and has poor corrosion resistance.
[0005] In the context of replacing steel with plastic, battery casing materials are also expanding in the direction of thermoplastic reinforced plastics. However, conventional plastic materials are more flammable than metal materials, which leads to a decrease in the safety factor of battery use and is not conducive to product application. Summary of the invention
[0006] The purpose of the present invention is to provide a special plastic composite material for new energy battery shells and a preparation method thereof, so as to improve the flame retardant performance of the battery shells.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] The present invention provides a special plastic composite material for a new energy battery shell, which includes the following raw materials by weight:
[0009] 70-80 parts of polyphenylene ether resin, 10-20 parts of high impact polystyrene resin, 5-15 parts of polyketone resin, 6-10 parts of polyamide resin, 4-8 parts of modified filler and 1-5 parts of meta-aramid fiber;
[0010] The modified filler is magnesium hydroxide / graphene intercalated organic modified montmorillonite.
[0011] Polyphenylene ether resin has the characteristics of light weight, high temperature resistance, corrosion resistance, good dimensional stability and low water absorption, and also has excellent mechanical strength. However, polyphenylene ether has problems with poor impact resistance and melt fluidity, and is difficult to process and shape. Polyphenylene ether resin and high-impact polystyrene resin have good compatibility, which can improve impact resistance and melt fluidity.
[0012] Polyketone resin has excellent heat resistance, chemical resistance, dimensional stability, can maintain its performance stable in acid and alkali solutions, and has excellent impact resistance.
[0013] Meta-aramid fiber has excellent flame retardant properties and can effectively disperse stress and avoid cracking of materials.
[0014] Furthermore, the preparation steps of the modified filler are as follows:
[0015] Step 1: Add the magnesium salt aqueous solution to the graphene oxide aqueous dispersion, stir at 50-60° C. for 10-30 min, let stand for 1-2 h, then drop the alkaline solution, continue stirring and reacting for 1-3 h after the addition is completed, centrifuge and wash, then freeze-dry to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0016] Step 2: Adjust the pH of the montmorillonite aqueous suspension to 4-5, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a CTAB solution, add it dropwise to the montmorillonite aqueous suspension while stirring, react at 60-90°C for 3-4h after the addition, filter, wash and dry to obtain an organic modified montmorillonite. The main component of montmorillonite is a layered silicate clay mineral with a 2:1 three-layer structure, and its unit cell is composed of two layers of silicon-oxygen tetrahedrons sandwiching a layer of aluminum-oxygen octahedrons. The tetrahedron and the octahedron are connected by shared oxygen atoms, the unit cells are stacked in parallel, and the A1 in the lattice is 2:1. 3+ and Si 4+ The ions are easily replaced by other low-valent cations to undergo isomorphous replacement, and are easily subjected to ion exchange reactions with alkyl quaternary ammonium salts or other organic cations to generate organic montmorillonite.
[0017] Step 3: Disperse the graphene oxide material with magnesium hydroxide loaded on the surface in a 60wt% ethanol aqueous solution to form a dispersion, add the organic modified montmorillonite into the 60wt% ethanol aqueous solution and ultrasonically disperse it to form a suspension, mix the dispersion and the suspension, react at 90-95°C for 1-2h, and filter and dry to obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite.
[0018] Furthermore, the magnesium salt aqueous solution is one of magnesium chloride and magnesium acetate aqueous solution, the solution concentration is 10-20 mmol / L, the alkaline solution is 0.05-0.1 mol / L sodium hydroxide aqueous solution, and the volume ratio of the magnesium salt aqueous solution to the alkaline solution is 1:0.2-0.8.
[0019] Furthermore, the concentration of the graphene oxide aqueous dispersion is 1-5 mg / mL. Graphene oxide has a two-dimensional layered structure, a large specific surface area, is easy to load, and can form a dense and continuous carbon layer during the combustion process, which plays a role of physical isolation and shielding, preventing oxygen from contacting fuel, thereby inhibiting the spread of flames.
[0020] Furthermore, the magnesium salt aqueous solution and the graphene oxide aqueous dispersion are in the form of m(Mg 2+ ):m(graphene oxide)=5-10:100 for mixing.
[0021] Furthermore, the montmorillonite aqueous suspension is a suspension formed by dissolving montmorillonite in water at a concentration of 10-15 mg / mL, and adjusting the pH to 2 mol / L of hydrochloric acid or sodium hydroxide solution.
[0022] Furthermore, in step 2, the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1-4:10, and hexadecyltrimethylammonium bromide is dissolved in water at a concentration of 6-24 mg / L to obtain a CTAB solution.
[0023] Furthermore, in step three, the dispersion and the suspension are mixed according to a mass ratio of 1:0.5-3 between the graphene oxide material with magnesium hydroxide loaded on the surface and the organic modified montmorillonite, the graphene oxide material with magnesium hydroxide loaded on the surface is dispersed in 60wt% ethanol at a concentration of 1-3mg / mL, and the organic modified montmorillonite is added to 60wt% ethanol at a concentration of 1-3mg / mL and ultrasonically dispersed to form a suspension.
[0024] The present invention also provides a method for preparing the above-mentioned special plastic composite material for new energy battery shell, comprising the following steps:
[0025] Step 1, adding meta-aramid fiber and modified thermal conductive filler into a mixer and mixing to obtain an additive;
[0026] Step 2: Add polyphenylene ether resin, polystyrene resin, polyketone resin, polyamide resin and additives into a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a special plastic composite material for new energy battery shells.
[0027] Furthermore, the melting temperature of the twin-screw extruder is 250-350°C.
[0028] Beneficial effects of the present invention:
[0029] (1) The present invention uses graphene oxide as a substrate to load magnesium hydroxide, and long-chain alkyl quaternary ammonium salt organically modifies montmorillonite to change its surface from hydrophilic to lipophilic, and utilizes the electrostatic interaction and steric hindrance effect between graphene oxide and montmorillonite to form an intercalation structure. By controlling the amount of magnesium hydroxide loaded, the degree of organic modification of montmorillonite, and the ratio of the graphene oxide material loaded with magnesium hydroxide to the organically modified montmorillonite, efficient dispersion of magnesium hydroxide, graphene oxide and montmorillonite in a high molecular polymer is achieved.
[0030] (2) Under combustion conditions, magnesium hydroxide decomposes under heat, absorbs heat and produces moisture. The intercalation structure of graphene oxide and montmorillonite increases the tortuosity of the path, which can delay the transfer of oxygen through the barrier effect of the "tortuous path". The synergistic effect of the three improves the flame retardant properties of the material. The high thermal conductivity of graphene oxide is conducive to rapid heat dissipation at high temperatures, making the plastic composite material have excellent flame retardant and thermal conductivity. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] Preparation of modified fillers:
[0034] Step 1: According to m(Mg 2+ ):m(graphene oxide)=5:100, add 10mmol / L magnesium chloride aqueous solution to 5mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60°C for 10min, let stand for 1h, then add dropwise 0.05mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.4:1, continue to stir and react for 1h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5°C for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0035] Step 2: Adjust the pH of 15 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 6 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 1:10. After the addition is completed, stir and react at 60°C for 4 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0036] Step 3: Disperse the surface-loaded magnesium hydroxide graphene oxide material in a 60wt% ethanol aqueous solution at a concentration of 3 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 1 mg / mL to a 60wt% ethanol aqueous solution for ultrasonic dispersion to form a suspension, mix the dispersion and the suspension at a mass ratio of 1:0.5 between the surface-loaded magnesium hydroxide graphene oxide material and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtration and drying.
[0037] Example 2
[0038] Preparation of modified fillers:
[0039] Step 1: According to m(Mg 2+ ):m(graphene oxide)=8:100, add 15mmol / L magnesium chloride aqueous solution to 3mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60℃ for 20min, let stand for 1.5h, then add dropwise 0.06mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.5:1, continue to stir and react for 2h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5℃ for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0040] Step 2: Adjust the pH of 15 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 6 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 1:10. After the addition is completed, stir and react at 60°C for 4 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0041] Step 3: Disperse the surface-loaded magnesium hydroxide graphene oxide material in a 60wt% ethanol aqueous solution at a concentration of 3 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 1 mg / mL to a 60wt% ethanol aqueous solution for ultrasonic dispersion to form a suspension, mix the dispersion and the suspension at a mass ratio of 1:0.5 between the surface-loaded magnesium hydroxide graphene oxide material and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtration and drying.
[0042] Example 3
[0043] Preparation of modified fillers:
[0044] Step 1. According to m(Mg2+):m(graphene oxide)=10:100, add 20mmol / L magnesium chloride aqueous solution to 1mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60°C for 30min, let stand for 2h, then add 0.1mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.5:1, continue to stir and react for 3h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5°C for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0045] Step 2: Adjust the pH of 15 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 6 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 1:10. After the addition is completed, stir and react at 60°C for 4 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0046] Step 3: Disperse the surface-loaded magnesium hydroxide graphene oxide material in a 60wt% ethanol aqueous solution at a concentration of 3 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 1 mg / mL to a 60wt% ethanol aqueous solution for ultrasonic dispersion to form a suspension, mix the dispersion and the suspension at a mass ratio of 1:0.5 between the surface-loaded magnesium hydroxide graphene oxide material and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtration and drying.
[0047] Example 4
[0048] Preparation of modified fillers:
[0049] Step 1: According to m(Mg 2+ ):m(graphene oxide)=8:100, add 15mmol / L magnesium chloride aqueous solution to 3mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60℃ for 20min, let stand for 1.5h, then add dropwise 0.06mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.5:1, continue to stir and react for 2h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5℃ for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0050] Step 2: Adjust the pH of 12 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 15 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 3:10. After the addition is completed, stir and react at 80°C for 3 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0051] Step 3: Disperse the surface-loaded magnesium hydroxide graphene oxide material in a 60wt% ethanol aqueous solution at a concentration of 3 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 1 mg / mL to a 60wt% ethanol aqueous solution for ultrasonic dispersion to form a suspension, mix the dispersion and the suspension at a mass ratio of 1:0.5 between the surface-loaded magnesium hydroxide graphene oxide material and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtration and drying.
[0052] Example 5
[0053] Preparation of modified fillers:
[0054] Step 1: According to m(Mg 2+ ):m(graphene oxide)=8:100, add 15mmol / L magnesium chloride aqueous solution to 3mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60℃ for 20min, let stand for 1.5h, then add dropwise 0.06mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.5:1, continue to stir and react for 2h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5℃ for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0055] Step 2: Adjust the pH of 10 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 24 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 4:10. After the addition is completed, stir and react at 90°C for 3 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0056] Step 3: Disperse the surface-loaded magnesium hydroxide graphene oxide material in a 60wt% ethanol aqueous solution at a concentration of 3 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 1 mg / mL to a 60wt% ethanol aqueous solution for ultrasonic dispersion to form a suspension, mix the dispersion and the suspension at a mass ratio of 1:0.5 between the surface-loaded magnesium hydroxide graphene oxide material and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtration and drying.
[0057] Example 6
[0058] Preparation of modified fillers:
[0059] Step 1: According to m(Mg 2+ ):m(graphene oxide)=8:100, add 15mmol / L magnesium chloride aqueous solution to 3mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60℃ for 20min, let stand for 1.5h, then add dropwise 0.06mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.5:1, continue to stir and react for 2h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5℃ for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0060] Step 2: Adjust the pH of 12 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 15 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 3:10. After the addition is completed, stir and react at 80°C for 3 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0061] Step 3: Disperse the graphene oxide material with magnesium hydroxide on the surface in a 60wt% ethanol aqueous solution at a concentration of 2 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 2 mg / mL to a 60wt% ethanol aqueous solution for ultrasonic dispersion to form a suspension, mix the dispersion and the suspension in a mass ratio of 1:2 between the graphene oxide material with magnesium hydroxide on the surface and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtering and drying.
[0062] Example 7
[0063] Preparation of modified fillers:
[0064] Step 1: According to m(Mg 2+):m(graphene oxide)=8:100, add 15mmol / L magnesium chloride aqueous solution to 3mg / mL graphene oxide aqueous dispersion, heat in a water bath and stir at 60℃ for 20min, let stand for 1.5h, then add dropwise 0.06mol / L sodium hydroxide aqueous solution, the volume ratio of sodium hydroxide aqueous solution to magnesium chloride aqueous solution is 0.5:1, continue to stir and react for 2h after the addition is completed, wash with anhydrous ethanol and deionized water after centrifugation, and freeze-dry at -5℃ for 6h to obtain a graphene oxide material with magnesium hydroxide loaded on the surface.
[0065] Step 2: Adjust the pH of 12 mg / mL montmorillonite aqueous suspension to 5 with 2 mol / L hydrochloric acid, weigh hexadecyltrimethylammonium bromide and dissolve it in water to obtain a 15 mg / L CTAB solution, and add the CTAB solution dropwise to the montmorillonite aqueous suspension with stirring according to the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite of 3:10. After the addition is completed, stir and react at 80°C for 3 hours, filter, wash with anhydrous ethanol and deionized water, and dry to obtain organic modified montmorillonite.
[0066] Step 3: Disperse the graphene oxide material with magnesium hydroxide on the surface in a 60wt% ethanol aqueous solution at a concentration of 1 mg / mL to form a dispersion, add the organic modified montmorillonite at a concentration of 3 mg / mL to a 60wt% ethanol aqueous solution and ultrasonically disperse to form a suspension, mix the dispersion and the suspension in a mass ratio of 1:3 between the graphene oxide material with magnesium hydroxide on the surface and the organic modified montmorillonite, react at 90°C for 2h, and obtain magnesium hydroxide / graphene intercalated organic modified montmorillonite after filtering and drying.
[0067] Example 8
[0068] This embodiment provides a special plastic composite material for new energy battery shells, which includes the following raw materials by weight:
[0069] 80 parts of polyphenylene ether resin, 10 parts of high impact polystyrene resin, 15 parts of polyketone resin, 6 parts of polyamide resin, 4 parts of modified filler prepared in Example 1 and 1 part of meta-aramid fiber
[0070] Preparation of plastic composites:
[0071] Step 1: weigh the raw materials according to the above proportions, add the meta-aramid fiber and the modified thermal conductive filler prepared in Example 1 into a stirrer and mix at 1200 r / min for 20 min to obtain an additive.
[0072] Step 2: Add polyphenylene ether resin, polystyrene resin, polyketone resin, polyamide resin and additives into a twin-screw extruder for melt blending, extrusion and granulation. The melting temperature of the twin-screw extruder is 250-350° C. After injection molding, a special plastic composite material for new energy battery shells is obtained.
[0073] Example 9
[0074] The difference from Example 8 is that the modified filler prepared in Example 1 replaces the modified filler prepared in Example 2, and the other steps and operations are the same as Example 8.
[0075] Example 10
[0076] The difference from Example 8 is that the modified filler prepared in Example 1 replaces the modified filler prepared in Example 3, and the other steps and operations are the same as Example 8.
[0077] Embodiment 11
[0078] The difference from Example 8 is that the modified filler prepared in Example 1 replaces the modified filler prepared in Example 4, and the other steps and operations are the same as Example 8.
[0079] Example 12
[0080] The difference from Example 8 is that the modified filler prepared in Example 1 replaces the modified filler prepared in Example 5, and the other steps and operations are the same as Example 8.
[0081] Example 13
[0082] The difference from Example 8 is that the modified filler prepared in Example 1 replaces the modified filler prepared in Example 6, and the other steps and operations are the same as Example 8.
[0083] Embodiment 14
[0084] The difference from Example 8 is that the modified filler prepared in Example 1 replaces the modified filler prepared in Example 7, and the other steps and operations are the same as Example 8.
[0085] Embodiment 15
[0086] This embodiment provides a special plastic composite material for new energy battery shells, which includes the following raw materials by weight:
[0087] 75 parts of polyphenylene ether resin, 15 parts of high impact polystyrene resin, 10 parts of polyketone resin, 8 parts of polyamide resin, 6 parts of modified filler prepared in Example 6 and 5 parts of meta-aramid fiber
[0088] Preparation of plastic composites:
[0089] Step 1: weigh the raw materials according to the above ratio, add the meta-aramid fiber and the modified thermal conductive filler prepared in Example 6 into a stirrer at 1200 r / min and mix for 20 minutes to obtain an additive.
[0090] Step 2: Add polyphenylene ether resin, polystyrene resin, polyketone resin, polyamide resin and additives into a twin-screw extruder for melt blending, extrusion and granulation. The melting temperature of the twin-screw extruder is 250-350° C. After injection molding, a special plastic composite material for new energy battery shells is obtained.
[0091] Example 16
[0092] This embodiment provides a special plastic composite material for new energy battery shells, which includes the following raw materials by weight:
[0093] 70 parts of polyphenylene ether resin, 20 parts of high impact polystyrene resin, 5 parts of polyketone resin, 10 parts of polyamide resin, 8 parts of modified filler prepared in Example 6 and 5 parts of meta-aramid fiber
[0094] Preparation of plastic composites:
[0095] Step 1: weigh the raw materials according to the above ratio, add the meta-aramid fiber and the modified thermal conductive filler prepared in Example 6 into a stirrer at 1200 r / min and mix for 20 minutes to obtain an additive.
[0096] Step 2: Add polyphenylene ether resin, polystyrene resin, polyketone resin, polyamide resin and additives into a twin-screw extruder for melt blending, extrusion and granulation. The melting temperature of the twin-screw extruder is 250-350° C. After injection molding, a special plastic composite material for new energy battery shells is obtained.
[0097] Comparative Example 1
[0098] Compared with Example 15, no modified filler is added to the raw materials of this comparative example, and other conditions and steps are the same as Example 15.
[0099] The performance tests were performed on the plastic composite materials prepared in Examples 8 to 16 and Comparative Example 1. The results are shown in Table 1.
[0100] The limiting oxygen index test is carried out according to ASTM D2863 standard.
[0101] The flame retardant grade test is carried out with reference to the vertical combustion method in "GBT2408-2021 Horizontal and vertical methods for determination of combustion performance of plastics".
[0102] Thermal conductivity testing is carried out with reference to ISO 22007-7:2023 Plastics - Determination of thermal conductivity and thermal diffusivity - Part 2: Transient planar heat source (hot plate) method.
[0103] The notched impact strength test is carried out with reference to "GBT 1043.2-2018 Determination of impact properties of plastic simply supported beams Part 2: Instrumented impact test".
[0104] Table 1
[0105]
[0106] As can be seen from Table 1, compared with Comparative Example 1, the plastic composite materials prepared in Examples 8-16 have better comprehensive properties. In Examples 8-10, due to the gradual increase in the ratio of magnesium hydroxide to graphene oxide in the preparation of the modified filler, its loading amount gradually increases, and the flame retardant properties of the prepared composite materials are improved; Compared with Example 8, Examples 11-12 increase the proportion of hexadecyltrimethylammonium bromide when modifying montmorillonite, increase the amount of long-chain alkyl on the surface of montmorillonite, and improve the compatibility of the modified filler with the polymer resin, which is more conducive to its dispersion. The flame retardant properties, thermal conductivity and impact resistance of the composite material are better than those of Example 8; Examples 13-14 increase the content of organic modified montmorillonite in the modified filler. Appropriately increasing the content can fully disperse the graphene oxide, and accordingly the performance of the composite material is significantly improved, but excessive increase in organic modified montmorillonite will reduce the thermal conductivity of the material.
[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A plastic composite material for new energy battery shell, characterized in that: The following raw materials are included by mass: 70-80 parts of polyphenylene ether resin, 10-20 parts of polystyrene resin, 5-15 parts of polyketone resin, 6-10 parts of polyamide resin, 4-8 parts of modified filler and 1-5 parts of meta-aramid fiber; The modified filler is magnesium hydroxide / graphene intercalated organic modified montmorillonite; The preparation steps of the modified filler are as follows: Step 1: adding a magnesium salt aqueous solution to an aqueous dispersion of graphene oxide, stirring at 50-60° C. for 10-30 min, standing for 1-2 h, and then dropping an alkaline solution, stirring and reacting for 1-3 h after the addition is completed, centrifugally washing, and freeze-drying to obtain a graphene oxide material with magnesium hydroxide loaded on the surface; Step 2, adjusting the pH of the montmorillonite aqueous suspension to 4-5, weighing hexadecyltrimethylammonium bromide and dissolving it in water, and adding it dropwise to the montmorillonite aqueous suspension while stirring, stirring and reacting at 60-90° C. for 3-4 hours after the addition, filtering, washing, and drying to obtain the organic modified montmorillonite; Step 3: Disperse the graphene oxide material with magnesium hydroxide loaded on the surface in an ethanol aqueous solution to form a dispersion, add the organically modified montmorillonite into the ethanol aqueous solution and ultrasonically disperse it to form a suspension, mix the dispersion and the suspension, react at 90-95° C. for 1-2 hours, and obtain magnesium hydroxide / graphene intercalated organically modified montmorillonite after filtering and drying.
2. A plastic composite material for new energy battery shell according to claim 1, characterized in that: The magnesium salt aqueous solution is one of magnesium chloride and magnesium acetate aqueous solution, the solution concentration is 10-20 mmol / L, the alkaline solution is 0.05-0.1 mol / L sodium hydroxide aqueous solution, and the volume ratio of the magnesium salt aqueous solution to the alkaline solution is 1:0.2-0.
8.
3. The special plastic composite material for new energy battery shell according to claim 1, characterized in that: The concentration of the graphene oxide aqueous dispersion is 1-5 mg / mL.
4. The special plastic composite material for new energy battery shell according to claim 1, characterized in that: The magnesium salt aqueous solution and the graphene oxide aqueous dispersion are in the form of m(Mg 2+ ):m(graphene oxide)=5-10:100 for mixing.
5. The special plastic composite material for new energy battery shell according to claim 1, characterized in that: The montmorillonite aqueous suspension is a suspension formed by dissolving montmorillonite in water at a concentration of 10-15 mg / mL.
6. The special plastic composite material for new energy battery shell according to claim 1, characterized in that: In step 2, the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1-4:
10.
7. The special plastic composite material for new energy battery shell according to claim 1, characterized in that: In step three, the dispersion and the suspension are mixed according to a mass ratio of the graphene oxide material with magnesium hydroxide loaded on the surface to the organic modified montmorillonite of 1:0.5-3.
8. A method for preparing a special plastic composite material for a new energy battery shell according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, adding meta-aramid fiber and modified thermal conductive filler into a mixer and mixing to obtain an additive; Step 2: Add polyphenylene ether resin, polystyrene resin, polyketone resin, polyamide resin and additives into a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a special plastic composite material for new energy battery shells.
9. The method for preparing a special plastic composite material for new energy battery shell according to claim 8, characterized in that: The melting temperature of the twin-screw extruder is 250-350°C.
Citation Information
Patent Citations
Cover for battery housing of high-voltage vehicle battery and battery housing
CN110492021A
High-frequency copper-clad plate of PPO resin base material and preparation method of high-frequency copper-clad plate
CN114714708A
Battery cell housings
WO2020074985A1